UPAYA MENINGKATKAN PEMBELAJARAN BOLA VOLI MENGGUNAKAN PENDEKATAN BERMAIN BOLA LIAR PADA SISWA KELAS IV SDN GAMER 01 KOTA PEKALONGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This study uses a Class Action Penilitian with the aim of improving learning outcomes volleyball serve under a loose ball play approach to improve the quality of student learning outcomes in the following learning process as indicated by the results of test performance, student attitudes and behavior of students better.From the results of research conducted, an increase in student learning outcomes of cycle 1 and cycle 2, both from an increase in the average value of service learning under volleyball mastery of learning outcomes and value. The average value of cycle 1 (75.33%) and the average cycle 2 (81.19%), so the increase from cycle 1 to cycle 2 is 5.86%. Increased movement to the bottom of the learning volleyball serve volleyball can be seen from the KKM (70.00) or 83.33% after the completion of the action in cycle 1 students who pass the value of learning as much as 10 of the 16 students (62.50%) and in cycle 2 were completed by 14 of 16 students completed a whole or by 83.33%.This is the conclusion of researchers suggest that service down to greater learning outcomes approach to playing volleyball through a loose ball in the fourth grade students of SD N Gamer 01 Lessons Pekalongan year 2012/2013, including both categories.